Public awareness and willingness to use automated external defibrillators in a metropolitan city - Lee, Jae Hyuk (Clin Exp Emerg Med, 2021)
OBJECTIVE: Early defibrillation is crucial for the survival of patients with out-of-hospital cardiac arrest. This study aimed to examine the trends and associated factors regarding public awareness and willingness to use automated external defibrillators (AEDs) through citywide surveys. METHODS: Three-round surveys were conducted in February 2012 (n=1,000), December 2016 (n=1,141), and December 2018 (n=1,001) among citizens in Daegu, South Korea, who were aged ≥19 years. The subjects were selected through a three-stage quota sampling. Awareness and willingness to use an AED were assessed in the three groups. The primary outcome was willingness to use AEDs. RESULTS: Of 3,142 respondents, 3,069 were eligible for analysis. The proportion of respondents who knew how to use AEDs increased from 4.7% in 2012 to 20.8% in 2018. Of the respondents in 2012, 2016, and 2018, 39.7%, 50.0%, and 43.2%, respectively, were willing to use an AED. Factors associated with willingness to use AEDs were male sex (adjusted odds ratio [AOR], 1.39; 95% confidence interval [CI], 1.10–1.75), cardiopulmonary resuscitation training experience in the previous 2 years (AOR, 1.80; 95% CI, 1.43–2.28), recognition of the Good Samaritan law (AOR, 1.45; 95% CI, 1.13–1.86), and awareness of how to use an AED (AOR, 4.40; 95% CI, 3.26–5.93). CONCLUSION: To increase willingness to use AEDs, education in AED use and the Good Samaritan law, along with re-education to maintain knowledge of AED use, should be considered.